Elections, Ideology, or Opposition? Assessing Competing Explanations of Judicial Spending: Mexico - Matthew C. Ingram (My University, 2016)
This study offers the first time series cross-section analysis of state courts in Mexico, explaining variation in judicial spending across Mexico’s 31 states from 1993 to 2009. Cutting against mainstream accounts of judicial empowerment that highlight electoral competition, I conclude that increasing competition, while a necessary precondition for the emergence of new political actors, has mixed results after a minimum, threshold level. Ideological motivations, especially on the left, enhance court budgets, and these motivations surmount the dampening, Downsian effect of competition. Further, the reduced effect of the PAN (National Action Party, former opposition party) and the increased positive effect of the PRI (Institutional Revolutionary Party, former national hegemon) since 2000 suggests ways in which former opposition parties can become less ideological (or more pro-regime), whereas former dominant parties can become more ideological (or more anti-regime). The results not only identify clear relationships but also highlight the complex electoral and partisan sources of policy change in authoritarian and emerging democratic regimes.